Adjuvant intravesical therapy in intermediate-risk non-muscle-invasive bladder cancer - Laukhtina, Ekaterina; Gontero, Paolo; Babjuk, Marko; Moschini, Marco; Teoh, Jeremy Yuen-Chun; Rouprêt, Morgan; Trinh, Quoc-Dien; Chlosta, Piotr; Nyirády, Péter; Abufaraj, Mohammad; Soria, Francesco; Klemm, Jakob; et al. (BJU international, 2024)
OBJECTIVE: To evaluate the impact of adjuvant therapy on oncological outcomes in patients with intermediate-risk non-muscle-invasive bladder cancer (NMIBC), as due to the poorly-defined and overlapping diagnostic criteria optimal decision-making remains challenging in these patients. PATIENTS AND METHODS: In this multicentre study, patients treated with transurethral resection of bladder tumour for Ta disease were retrospectively analysed. All patients with low- or high-risk NMIBC were excluded from the analysis. Associations between adjuvant therapy administration with recurrence-free survival (RFS) and progression-free survival (PFS) rates were assessed in Cox regression models. RESULTS: A total of 2206 patients with intermediate-risk NMIBC were included in the analysis. Among them, 1427 patients underwent adjuvant therapy, such as bacille Calmette-Guérin (n = 168), or chemotherapeutic agents, such as mitomycin C or epirubicin (n = 1259), in different regimens up to 1 year. The median (interquartile range) follow-up was 73.3 (38.4-106.9) months. The RFS at 1 and 5 years in patients treated with adjuvant therapy and those without were 72.6% vs 69.5% and 50.8% vs 41.3%, respectively. Adjuvant therapy was associated with better RFS (hazard ratio [HR] 0.79, 95% confidence interval [CI] 0.70-0.89, P < 0.001), but not with PFS (P = 0.09). In the subgroup of patients aged ≤70 years with primary, single Ta Grade 2 <3 cm tumours (n = 328), adjuvant therapy was not associated with RFS (HR 0.71, 95% CI 0.50-1.02, P = 0.06). While in the subgroup of patients with at least one risk factor including patient age >70 years, tumour multiplicity, recurrent tumour and tumour size ≥3 cm (n = 1878), adjuvant intravesical therapy was associated with improved RFS (HR 0.78, 95% CI 0.68-0.88, P < 0.001). CONCLUSION: In our study, patients with intermediate-risk NMIBC benefit from adjuvant intravesical therapy in terms of RFS. However, in patients without risk factors, adjuvant intravesical therapy did not result in a clear reduction in the recurrence rate.
Keywords: Non-Muscle Invasive Bladder Neoplasms; invazivní růst nádoru; Neoplasm Invasiveness; Administration, Intravesical; přežití bez známek nemoci; BCG Vaccine; retrospektivní studie; Humans; Disease-Free Survival; lidé středního věku; nádory močového měchýře; Middle Aged; mitomycin; BCG; adjuvant; epirubicin; chemotherapy; Chemotherapy, Adjuvant; nádory močového měchýře neinvadující svalovinu; mužské pohlaví; Epirubicin; NMIBC; Urinary Bladder Neoplasms; ženské pohlaví; aplikace intravezikální; lidé; Cystectomy; adjuvantní chemoterapie; cystektomie; intravesical; Mitomycin; BCG vakcína; Aged; senioři; Male; Retrospective Studies; Female